Unprecedented W2(0) quadruply bonded complex supported by π-donor ligands. Issue 20 (17th February 2016) - Ventura, K.; Prat, J. R.; Aguirre Quintana, L. M.; Goos, A.; Villagran, D.
Abstract : A quadruply bonded complex W2 (DippF)2 K2 with a W2 (0) core was synthesized and structurally characterized. Abstract : A quadruply bonded complex W2 (DippF)2 K2 with a W2 (0) core was synthesized and structurally characterized. The observed W–W distance of 2.407(1) Å and DFT calculations are consistent to the unprecedented electronic structure in D 2h symmetry of σ 2 π 2 π 2 δ 2 δ 2 δ* 2 where the HOMO is the δ* orbital.